Pelatihan Pembuatan Tepung Pisang dan Olahannya Dalam Upaya Pemanfaatan dan Peningkatan Nilai Ekonomi Pangan Lokal Papua - Vita Purnamasari; I Made Budi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Bananas are a fruit commodity that produces the most in Jayapura Regency. Processing bananas into flour is one way to increase the selling value of banana commodities and increase their utilization into banana derivative products. The aim of the training is to utilize local Papuan food, namely bananas, to increase the economic value of local Papuan food. The training activities provide knowledge and insight to the public regarding banana derivative products, namely flour and preparations made from banana flour to increase economic independence. Local Papuan bananas, such as gray bananas, have the potential to be made into flour and their preparations using simple technology available in the community so that they have the potential to be developed to increase the economic value of local Papuan food.Â Keyword: banana flour; Papuan local varieties of bananas; processed banana flour; local food.